Efficacy of a single ultrasound-guided injection of high molecular weight hyaluronic acid combined with collagen tripeptide in patients with knee osteoarthritis and chondrocalcinosis - Porta, Francesco; Filippucci, Emilio; Cipolletta, Edoardo; La Grua, Marco; Barni, Xenia; Sirotti, Silvia; Vreju, Florentin Ananu (Frontiers in Medicine, 2024)
Introduction Osteoarthritis (OA) and calcium pyrophosphate dihydrate crystal deposition (CPPD) often co-exist, this resulting in a clinical condition characterized by amplified inflammation and more severe and faster cartilage degeneration compared to osteoarthritis alone. Our study aims to explore the efficacy of a therapeutic approach that addresses both conditions, using a combination of a high molecular weight hyaluronic acid (HMWHA) and collagen tripeptide (CT). Additionally, safety profile and baseline characteristic predictive value were evaluated.Methods: We conducted a retrospective study on patients diagnosed with symptomatic knee OA (KOA) and CPPD treated by ultrasound (US) guided intraarticular injections of HMWHA-CT in the outpatient clinics of the